Роль полиморфизма A1470T гена MCT1 в развитии выносливости и скорости у спортсменов = The role of A1470T gene polymorphism MCT1 in development speed and endurance in athletes - Kozyrev, A. V.; Gozhenko, A. I.; Sikora, K.; Zukow, W. (Journal of Education, Health and Sport, 2016)
Kozyrev A. V. Gozhenko A. I., Sikora K., Zukow W. Роль полиморфизма A1470T гена MCT1 в развитии выносливости и скорости у спортсменов = The role of A1470T gene polymorphism MCT1 in development speed and endurance in athletes. Journal of Education, Health and Sport. 2016;6(10):253-262. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.161067 http://ojs.ukw.edu.pl/index.php/johs/article/view/3938 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.10.2016. Revised 02.10.2016. Accepted: 15.10.2016. РОЛЬ ПОЛИМОРФИЗМА A1470T ГЕНА MCT1 В РАЗВИТИИ ВЫНОСЛИВОСТИ И СКОРОСТИ У СПОРТСМЕНОВ The role of A1470T gene polymorphism MCT1 in development speed and endurance in athletes Kozyrev A. V. Gozhenko A. I., Sikora K., Zukow W. Козырев А. В. Гоженко А. И., Sikora K., Zukow W. International Technological University "Politehnica" Nikolaev (Mykolaiv) SE Research Institute of Medicine Transport (Odessa) WSG w Bydgoszczy UKW w Bydgoszczy Международный технологический университет «Николаевская политехника» (г. Николаев) ГП НИИ Медицины транспорта (г. Одесса) WSG w Bydgoszczy UKW w Bydgoszczy Ключевые слова: полиморфизм, A1470T, ген, MCT1, выносливость, скорость, спортсмен Key words: polymorphism, A1470T, gene, MCT1, speed, endurance, sportsman Резюме С усовершенствованием методов молекулярной биологии появилась возможность определения спортивных задатков с использованием генетических маркеров уже при рождении человека. В связи с этим внедрение молекулярно-генетических методов в практику спортивной науки существенно повысило прогностические возможности спортивного отбора и профессиональной ориентации и привело к формированию нового раздела спортивной науки – молекулярной генетики спорта [1]. Целью исследования было определение возможности проведения спортивного отбора в академическую греблю и лёгкую атлетику на основании результатов молекулярно-генетического анализа полиморфизма A1470T гена MCT1. Объектом исследования была физическая работоспособность спортсменов, специализирующихся в академической гребле и лёгкой атлетике. Предметом исследования были молекулярно-генетические факторы обуславливающие физическую работоспособность спортсменов. В исследовании приняло участие 40 человек – 2 группы по 20 человек в каждой. Опытную группу составили профессиональные спортсмены высокой квалификации, специализирующиеся в академической гребле. На момент проведения исследований, 15 спортсменов были мастерами спорта и 5 – мастерами спорта международного класса. Контрольную группу составили профессиональные спортсмены высокой квалификации, специализирующиеся в лёгкой атлетике, а именно в беге на спринтерские дистанции. На момент проведения исследований, 12 спортсменов были мастерами спорта и 8 – мастерами спорта международного класса. Возраст участников обоих групп составил от 19 до 25 лет. Полученные результаты позволяют сделать предположение о том, что превалирующая у спортсменов-гребцов аллель, является молекулярно-генетическим критерием склонности к выполнению физической деятельности, связанной с проявлением выносливости и связана с предрасположенностью к занятиям академической греблей. Превалирующая у спортсменов-легкоатлетов аллель, является молекулярно-генетическим критерием склонности к выполнению физической деятельности, связанной с проявлением скоростных качеств и связана с предрасположенностью к занятиям легкой атлетикой, а именно её спринтерскими беговыми дисциплинами. Данные аллели, могут быть рекомендованы в качестве диагностических генетических маркеров для оценки склонности к развитию и проявлению выносливости и скорости. Summary Improvements in methods in molecular biology, it became possible to determine sporting inclinations using genetic markers already at birth man. In this connection, the introduction of molecular genetic methods in the practice of Sport Science has significantly increased predictive ability of sports and vocational guidance and selection led to the formation of a new section of sports science-molecular genetics sport [1]. The aim of the study was to determine the feasibility of holding sports selection in academic rowing and athletics on the basis of the results of molecular-genetic analysis of A1470T gene polymorphism MCT1. The object of the study was the physical performance of athletes specialised in rowing and athletics. The subject study were molecular genetic factors behind physical performance of athletes. In a study of 40 people participated-2 unit for 20 people each. Experimental group consisted of highly qualified professional athletes specialised in rowing. At the time of research, the 15 athletes were masters of sports and 5-Masters of sports of the international class. A control group consisted of professional athletes of high qualification, specializing in athletics, namely in the Sprint distance. At the time of research, 12 athletes were masters of sports and 8-masters of sports of the international class. Age of participants in both groups ranged from 19 to 25 years. The results lead to the assumption that prevailing in athletes-rowers allele, is a molecular genetic criterion propensity to perform physical activities related to the display of endurance and is associated with a predisposition to rowing lessons. The prevailing in athletes-athletes allele, is a molecular genetic propensity to fulfill the criterion of physical activity associated with the appearance of high-speed characteristics and is associated with a predisposition to athletics, namely its cross-country sprint disciplines. These alleles can be recommended as a diagnostic genetic markers for assessing the propensity for the development and manifestation of endurance and speed.